Relevansi Sarjana IAT terhadap Pembentukan Karakter Qurani melalui Program Tahfiz di Rumah Tahfiz Miftahul Jannah Medan Tembung - Wulan Angraini; Ardiansyah Ardiansyah (CV. ALIM'SPUBLISHING, 2026)
This research begins with the importance of education based on the Qur'an to shape the religious character of students amidst the progress of the times and the decline of moral values ​​​​among the younger generation. The tahfiz program is one of the effective steps in instilling Qur'anic values, such as discipline, responsibility, patience, and good character. In its implementation, Bachelor of Qur'anic Science and Tafsir (IAT) is considered to have the right competence because they master the reading, memorization, and understanding of the meaning of the verses of the Qur'an. This study aims to determine the relevance and role of IAT Bachelors in shaping Qur'anic character through the tahfiz program at the Miftahul Jannah Medan Tembung Tahfiz House. The method used was qualitative research, using descriptive methods and case studies. Data were obtained through observations, interviews, and documentation, then analyzed using the steps of data reduction, data presentation, and drawing conclusions. The results of the study indicate that IAT Bachelors have a crucial role as teachers, mentors, and role models in instilling Qur'anic values ​​​​in students. Through structured memorization learning methods and the instilling of Islamic behavior, students can develop Quranic character. Therefore, the presence of IAT scholars has proven relevant and significantly contributes to the success of the memorization program and the formation of Quranic character at Rumah Tahfiz.